Powder X-ray diffraction of Metastudtite, (UO2)O2(H2O)2. Issue 1 (17th February 2016) - Rodriguez, Mark A.; Weck, Philippe E.; Sugar, Joshua D.; Kulp, Thomas J.
Abstract : There has been some confusion in the published literature concerning the structure of Metastudtite (UO2 )O2 (H2 O)2 where differing unit cells and space groups have been cited for this compound. Owing to the absence of a refined structure for Metastudtite, Weck et al . (2012) have documented a first-principles study of Metastudtite using density functional theory (DFT). Their model presents the structure of Metastudtite as an orthorhombic (space group Pnma ) structure with lattice parameters of a = 8.45, b = 8.72, and c = 6.75 Å. A Powder Diffraction File (PDF) database entry has been allocated for this hypothetical Metastudtite phase based on the DFT modeling (see 01-081-9033) and aforementioned Dalton Trans. manuscript. We have obtained phase pure powder X-ray diffraction data for Metastudtite and have confirmed the model of Weck et al . via Rietveld refinement (seeFigure 1 ). Structural refinement of this powder diffraction dataset has yielded updated refined parameters. The new cell has been determined as a = 8.411(1), b = 8.744(1), and c = 6.505(1) Å; cell volume = 478.39 Å3. There are only subtle differences between the refined structure and that of the first-principles model derived from DFT. Notably, the b -axis is significantly contracted in the final refinement as compared with DFT. There were also subtle changes to the U1, O1, and O3 atom positions. Tabulated powder diffraction data (d's and I's) for the Metastudtite have been derived from the refined model and these new values can serve to augment the PDF entry 01-081-9033 with a more updated entry based on observed X-ray powder diffraction data.